Assessing the Health Level of Islamic Commercial Banks for the Period 2018-2022: RGEC Analysis - Riza Kartika Dewi; Meilana Widyaningsih (UIN Siber Syekh Nurjati Cirebon, 2024)
Â Public perception of the stability and reliability of a bank is strongly influenced by various indicators of bank health, which in turn will affect their decision to choose the bank. This study aims to analyze the health level of Islamic Commercial Banks in Indonesia during 2018-2022 with the RGEC approach. The research method uses quantitative descriptive techniques on secondary data from financial statements and GCG reports from Islamic Commercial Banks between 2018 and 2022. The findings of this study reveal that overall the Islamic Commercial Bank is at PK-3 with a fairly good predicate. The risk profile component was evaluated, as measured by the NPF and FDR ratios obtained PK-2 with a healthy predicate. The Good Corporate Governance (GCG) component, evaluated through self-assessment analysis obtained PK-2 with a healthy predicate. In the earnings aspect, which is measured through the return on assets (ROA) ratio, obtaining PK-3 is quite healthy. However, the Operating Cost-Operating Income (BOPO) ratio is categorized as unhealthy with PK-5. Meanwhile, the assessment of the capital component received PK-1 with a very healthy predicate.Keywords: Bank health level, RGEC, Islamic Commercial Bank